2017
DOI: 10.1007/978-1-4939-7477-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of Hsf1, 2, and 4 Genes in Mice

Abstract: i. Summary/Abstract Heat shock transcription factors (Hsfs) regulate transcription of heat shock proteins as well as other genes whose promoters contain heat shock elements (HSEs). There are at least five Hsfs in mammalian cells, Hsf1, Hsf2, Hsf3, Hsf4 and Hsfy 1–6. To understand the physiological roles of Hsf1, Hsf2 and Hsf4 in vivo, we generated knockout mouse lines for these factors 7–9. Number of other laboratories have also generated Hsf1 10, 11, Hsf2 12, 13 and Hsf4 14 knockout mouse models. In this chap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Unlike a single HSF in invertebrates, six HSFs have been found in mammals (HSF1, HSF2, HSF3, HSF4, HSFX, and HSFY), and plants are known to express more than thirty different HSFs (for comprehensive reviews see [2,12,13]). Among the five human HSFs, the functions of HSF1, HSF2, and HSF4 have been most extensively studied [1,14,15]. Since the structural domains in HSF proteins have been described in great detail in a recent review [2], they are only briefly summarized here.…”
Section: Domain Structure In Hsfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike a single HSF in invertebrates, six HSFs have been found in mammals (HSF1, HSF2, HSF3, HSF4, HSFX, and HSFY), and plants are known to express more than thirty different HSFs (for comprehensive reviews see [2,12,13]). Among the five human HSFs, the functions of HSF1, HSF2, and HSF4 have been most extensively studied [1,14,15]. Since the structural domains in HSF proteins have been described in great detail in a recent review [2], they are only briefly summarized here.…”
Section: Domain Structure In Hsfsmentioning
confidence: 99%
“…Studies using HSF-null mice have made it possible to further identify the physiological and developmental processes in which HSF1, HSF2, and HSF4 are involved. All HSF-null mice are viable but display distinct phenotypes, such as abnormalities in sensory organs and the brain, while others have similar phenotypes, such as impaired fertility, for details, see below [14,55,56]. Of note, HSF-null mice are regarded as a representative model, since murine HSFs display more than 84% identical amino acid sequence to human HSFs.…”
Section: Hsfs As Developmental Factorsmentioning
confidence: 99%
“…More recently, it has been shown that HSF1 is abundant in the nuclei of mammary tumor cells in clinical biopsy samples, indicating constitutive activation of the heat shock response in cancer [38]. Perhaps most significantly, it has been shown that knockout of HSF1 in mouse tumor models, including p53-deficient or Her2-overexpressing spontaneous cancer, severely curtails tumor growth [13,[45][46][47][62][63][64]. These studies provide strong evidence for an important causal and essential role for the factor in tumorigenesis.…”
Section: Roles For Hsf1 In Cellular Processes Associated With Transfomentioning
confidence: 90%
“…The importance of the HSR is underscored by the existence of more than five HSF paralogs in humans [13], although only HSF1, HSF2, and HSF4 have been reported in the cancer literature. HSF2 influences neurodevelopment and is able to amplify the HSR in collaboration with HSF1 [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation